Qualitative and quantitative modifications of von Willebrand factor in patients with essential thrombocythemia and controlled platelet count. (22nd May 2015) - Lancellotti, S.; Dragani, A.; Ranalli, P.; Petrucci, G.; Basso, M.; Tartaglione, R.; Rocca, B.; De Cristofaro, R.
Summary Background Essential thrombocythemia (ET) is characterized by increased platelets and prevalent thrombosis. An acquired von Willebrand factor (VWF) disease has been hypothesized and inconsistently associated with extreme thrombocytosis or rare bleeding in ET. Whether VWF is modified in ET patients with controlled platelet count remains unclear. Objectives We studied different VWF‐ and platelet‐associated parameters in ET patients treated according to current recommendations. Patients/Methods Sixty‐nine ET patients (M = 29; median age, 62 [48–70] years; platelets, 432 [337–620] × 103 μL−1), 69 matched controls and 10 subjects with reactive thrombocytosis (RT) were studied. VWF:antigen (Ag), activity (act), electrophoretic patterns, VWF:propeptide, plasma glycocalycin (GC), glycoproteinV (GpV), ADAMTS‐13, elastase, C‐reactive protein and serum thromboxane (TX)B2 were measured. Results In ET patients, VWF:Ag was increased by 31 ± 13% vs. controls (P < 0.01), without dependence of blood groups, while VWF:act was reduced by 21 ± 12% vs. controls and by 50 ± 24% vs. RT (P < 0.01). The VWF:act/VWF:Ag ratios in ET were reduced by 35 ± 17% vs. controls and RT patients (P < 0.001) and significantly associated with: immature or total platelet counts, GC, GpV and TXB2. In multivariable analysis, only GC inversely predicted ET patients' VWF:act/VWF:Ag ratios (β = −0.42, P = 0.01). By electrophoresis analyses, high‐molecular‐weight VWF multimers were variably reduced with atypical cleavage bands in ET only. VWF:propeptide, ADAMTS‐13 and elastase levels were normal in ET patients. Platelet‐associated ADAM‐10 and ADAM‐17 hydrolyzed VWFm in vitro, showing patterns similar to those in ET samples. Conclusions In ET patients with controlled platelet counts, the VWF:act/VWF:Ag ratio is decreased and predicted by GC, a product of platelet activation. ADAM‐10 and/or ADAM‐17 might be involved. In vivo platelet activation, which characterizes ET, might contribute to disease‐specific VWF alterations.